DESAIN MEDIA EDUKASI ANIMASI INTERAKTIF CARA PEMANFAATAN LIMBAH SAMPAH BERBASIS MACROMEDIA FLASH 8 - Sidik Sidik (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
Garbage is a problem that will always exist and will accompany the increasing population growth in the region. Indifference to the problems of waste management results in the degradation of environmental quality that does not give comfort to live, so it will degrade the quality of public health. Subjects in this study is the design of educational media (learning) based on how the use of interactive animations using Macromedia Flash 8 bins. The object of research is addressed to students grade IV to VI. With each of the 15 students assigned per class to be used as samples taken at random, so there are a total of 45 respondents. The frequency distribution tables and histograms show the categorization of students' views in 4 aspects are very well located at intervals of> 86. Both categories are in the interval 76-85. Less category is in the interval 56-75. Category sorely lacking is in the interval <55. From these results it can be said that the students have a positive outlook on Media Education Animation Waste Utilization Method Based Interactive Macromedia Flash 8 with the option to be in the range of categories of good and very good